SOCIAL ENTREPRENEURSHIP IN KAZAKHSTAN AS A NEW MODEL OF SUSTAINABLE SOCIAL CHANGE: TRENDS, CHALLENGES AND DEVELOPMENT PROSPECTS (Journal of Economic Research & Business Administration, 2018)
Social entrepreneurship is gaining popularity throughout the world. Basically, experts have identified four features of social entrepreneurship. Firstly, it is the social impact, i.e. the activity of the company should be aimed at mitigating the existing social problems. Secondly, it must be characterized by innovation, that is, in their work the company must use new and unique methods of work. Thirdly, it must have signs of financial stability. Finally, the fourth feature is scalability, i.e. the possibility to transfer their skills to other companies, markets and even countries. The adoption of a new law in Kazakhstan Republic of Kazakhstan «On public-private partnership» provides for the removal of restrictions on the areas of public-private partnership, to create all conditions for the effective implementation of social projects, which leads to an increase in the number of social entrepreneurs. Within the framework of the idea of «Almaty – the city of social entrepreneurship» in Almaty Management University on the basis of the Centre for Social Entrepreneurship created «ecosystem of support» of social entrepreneurship.